PERATURAN DAERAH NOMOR 6 TAHUN 2016 TENTANG BANTUAN HUKUM UNTUK MASYARAKAT MISKIN DI KOTA SORONG - Ulupalu, Rauf (Fakultas Hukum Universitas Narotama, 2025)
Regional Regulation Number 6 of 2016 Concerning Legal Aid for the Poor in Sorong City in providing free legal aid for the poor in reality has not been able to run well because of deviations in its practice. These deviations can still be found at the beginning of the criminal trial process, making exceptions, making replies, pleas, in examining witnesses and in carrying out other defenses. The obstacles experienced by the Legal Aid Institution in providing free legal aid for the poor in the criminal trial process at the Sorong District Court, there are internal and external obstacles, namely internal obstacles from the legal counsel themselves and external obstacles from the public prosecutor, judges and the community who receive legal assistance. Overcoming the obstacles experienced by Advocates in providing free legal aid for the poor can be overcome with 3 legal factors as a solution, namely, the legal substance factor, legal structure and legal culture.